Randomized clinical trials of nonpharmacological treatments - Boutron, Isabelle; Ravaud, Philippe; Moher, David, 1957- (Boca Raton : Chapman and Hall/CRC, 2012)
"Nonpharmacological treatments include a wide variety of treatments such as surgery, technical procedures, implantable devices, nonimplantable devices, rehabilitation, psychoteherapy, and behavioral interventions. This book focuses on the methods of assessing nonpharmacological treatments, highlighting specific issues and discussing all possible design of trials. It provides practical examples to underline the issues and solutions in assessing nonpharmacological treatment in trials. Arguably the first book to exclusively explore this topic, it discusses various categories of treatments from surgical procedures to psychotherapy"--Provided by publisher.
pt. 1. Assessing nonpharmacological treatments : theoretical framework -- pt. 2. Assessing nonpharmacological treatments : practice examples.
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Clinical trials; Medicine -- Research; Biology -- Research; Statistics; Electronic books